Using IR thermography to determine the heat flux removed by spray cooling a high-temperature metallic surface - Pedotto, Cristina (Kansas State University, 2008)
A significant body of literature exists for experiments in spray cooling applications that utilize one-dimensional heat transfer through a metal ingot to determine the average surface heat flux. Due to inherent non-uniformities in spray distributions, measurements that account for the two-dimensional effects are required. In this study, an infrared (IR) camera was used to capture the two-dimensional temperature distribution formed when spraying an electrically heated NiChrome surface with three different fluids. IR thermography captured the thermal response of the un-sprayed side of a 0.005-inch (0.125mm) think strip of NiChrome exposed to spray from a 90° full-cone nozzle at low mass fluxes (0.025 – 0.045 lb/ft[superscript]2-s / 0.122 – 0.220 kg/m[superscript]2-s) from a distance of approximately 5 to 11 inches (13 to 28cm). Results were measured for surface average temperatures ranging from 150 to 600°F (65 – 315°C).
Keywords: Spray Cooling; Phase Change; Heat Transfer; Engineering, General (0537); Engineering, Mechanical (0548)